FUNGSI STRATEGIS SISTEM INFORMASI DALAM MEMPERKUAT FONDASI CASHLESS SOCIETY YANG AMAN DAN INKLUSIF DI INDONESIA - Najwa Aulia Kartika; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Digital transformation in the financial sector has become one of the main pillars of national economic development. The utilization of integrated information systems has accelerated the realization of a cashless financial ecosystem in Indonesia. This study aims to analyze the role of information systems in strengthening transaction security and expanding financial inclusion toward a safe and equitable cashless society. The research method used is a qualitative descriptive literature study by reviewing various scientific sources, official reports from Bank Indonesia, the Financial Services Authority (OJK), and the Ministry of Communication and Information. The results show that information systems play an important role in transaction efficiency, financial transparency, and strengthening the foundation of a cashless society in Indonesia. However, challenges such as cybersecurity risks, digital inequality, and low financial literacy remain major obstacles. Therefore, strengthening technological infrastructure, digital literacy education, and personal data protection should become national priorities in developing an inclusive and sustainable cashless society.